Draft Annual Plan 1990-91 Government of Punjab - Planning Commission (Planning Commission, 1990)
Plan 1990-91 Development Expenditure Draft Annual Plan 1990-91 Statement II Schemes Outlay and Expenditure Head Agriculture Draft Annual Plan 1990-91 Statement II: Schemes Outlay and Expenditure Head : Soil Conservation Draft Annual Plan 1990-91 Statement : Schemes Outlay and Expenditure Head : Animal Husbandry Draft Annual Plan 1990-91 Statement -II —Schemes Outlay and Expenditure Head : Dairying and Milk Supply Bras Annual Plan 1990-91 Statement11— Schemes Outlay and Expenditure Head : Fisheries Draft Annual Plan 1990-91 Statement 11 : Schemes Outlay and Expenditure Head ; Forests Draft Annual Flan 1990-91 Statement 11 Schemes Outlay and Expenditure Head Cooperation Draft Annual Plan 1990-91 Statement 11 Schemes Outlay and Expenditure Head: Community Development and Panchayats.
Government of Punjab, Department of Planning